Development of a novel pretreatment protocol for the efficient isolation and enrichment of honey proteome using pine honey and the hypopharyngeal glands of Apis mellifera L. - KÖK YETİMOĞLU, ECE (My University, 2022)
A versatile sample pretreatment method for the honey matrix is still needed for any proteomic-based investigations. Invertase and diastase are the most important enzymes in the maturation of pine honey and the origin of these enzymes are attributed to the bee\"s hypopharyngeal glands (HPG). In our study, we aimed to isolate and enrich these enzymes as model proteins representing the honey proteome in an efficient and practical way. As authenticity comparison, isolating the same enzymes from HPG samples was also accomplished. For yielding pine honey crude protein isolate, as a tandem two-step approach, stirred cell ultrafiltration followed by centrifugal ultrafiltration (CUF) protocol was determined after experimental optimization. HPGs were dissected from the Apis mellifera L. and proteins were extracted by using a bead beater followed by concentration using CUF. Protein profiles of pine honey and HPG were compared by SDS-PAGE. The resulting protein concentrations, enzyme activities, and the cleaning efficiencies of the applied techniques were evaluated and optimized using the Bradford assay, modified enzyme activity assays, and sugar profiling method developed at HPLC-RID. The novel pretreatment method provided invertase at 1055.1 U/kg activity and diastase at 693.3 Shade U/g activity with yields of 900.9% and 2432.6%, respectively. The final crude protein isolate can be interpreted as reference material at any authenticity and quality assays of honey. The obtained crude protein extract will pave the way for high throughput proteomic investigations at the honey matrix. Furthermore, this template methodology could be scaled up in the industry for natural enzyme production.
Keywords: Tarımsal Bilimler; Ziraat; Gıda Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Food Engineering; Engineering and Technology; GIDA BİLİMİ VE TEKNOLOJİSİ; Tarım Bilimleri; Tarım ve Çevre Bilimleri (AGE); FOOD SCIENCE & TECHNOLOGY; AGRICULTURAL SCIENCES; Agriculture & Environment Sciences (AGE); Food Science; Life Sciences; Pine honey; Protein isolation; Enzyme enrichment; Invertase; Diastase; INVERTASE ACTIVITY; ALPHA-GLUCOSIDASE; FLORAL ORIGIN; AMYLASE; QUANTIFICATION; PURIFICATION; EXPRESSION; PROTEINS; MARKERS; SAMPLES; Pine honey; Protein isolation; Enzyme enrichment; Invertase; Diastase